Objectives and Instruments of Innovation Policies in Costa Rica - Orozco-Barrantes, Jeffrey (2020)
This study aims to determine the theoretical approach from which the policies and instruments proposed by the main public entities immersed in the innovation process in Costa Rica (MAG, MEIC, MICITT, Comex- Procomer, public universities) have been designed. We start from the identification of the objectives that these public actors have set in advance. What is the rationale behind the design and application of policies to promote innovation in the country? Do the objectives coincide with the objectives of strengthening the fundamental components of a National Innovation System? As stated by Kulman et al. (2010), it is ideal that there is an adequate coordination between the theory to formulate innovation policies and the practice of innovation. We found that some theoretical objectives are contemplated by all the public actors addressed (such as providing results in R&D and generating competences through learning), while other objectives are incorporated in a smaller dimension (forming new markets, articulate quality requirements and incubate companies). But there is a poor coordination among the actors.